2020
DOI: 10.3390/su12031204
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and Horizontal Profiles of Particulate Matter and Black Carbon Near Elevated Highways Based on Unmanned Aerial Vehicle Monitoring

Abstract: Highways passing through cities cause additional pollution inside the city. However, most of the current studies are using ground-based monitoring technologies, which make it difficult to capture the dispersion patterns of pollutants near elevated highways or transportation interchanges. The purpose of this study is to discover short-term three-dimensional variations in traffic-related pollutants based on unmanned aerial vehicles. The monitoring locations are at suburban elevated highway and transportation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 41 publications
(47 reference statements)
0
8
0
Order By: Relevance
“… 7 Data from roadside monitors are typically dropped from analyses of the impact of air pollution on human health ( Ostro 2004 , 36). Although major roads like Carrera 7ma in Bogotá generate high ambient concentrations of pollutants in the immediate surrounding area, these concentrations fall precipitously within a few hundred meters (e.g., Cao et al, 2020 ). As a result, including observations from Móvil 7ma monitoring station could bias our econometrically estimated treatment effect estimates downward (larger negative effect).…”
mentioning
confidence: 99%
“… 7 Data from roadside monitors are typically dropped from analyses of the impact of air pollution on human health ( Ostro 2004 , 36). Although major roads like Carrera 7ma in Bogotá generate high ambient concentrations of pollutants in the immediate surrounding area, these concentrations fall precipitously within a few hundred meters (e.g., Cao et al, 2020 ). As a result, including observations from Móvil 7ma monitoring station could bias our econometrically estimated treatment effect estimates downward (larger negative effect).…”
mentioning
confidence: 99%
“…We tested the effects of quartiles of distance to roads on biomarker concentrations for two reasons: (1) the distance of a participant’s residence to the highway is not evenly distributed. (2) Previous studies have shown that the levels of many pollutants such as black carbon decay rapidly within 100 m of a highway, , meaning that further increasing the distance would not result in lower levels of pollutants. Alpha was set at 0.05, and all tests were two-tailed.…”
Section: Methodsmentioning
confidence: 99%
“…All the pollutants dropped to lower concentration levels after 100 m horizontally. However, at the location with the more complicated road configuration, the distance exceeded 200 m [7].…”
Section: Present State Of Knowledgementioning
confidence: 97%
“…The measurements using a tower are independent of measurement duration and allow for the comparison of measurement devices and offer more mounting space. However, the drawbacks include low vertical resolution, measurement height, and mobility [7]. Aircraft are mainly used to perform measurements at the altitude range of about 1-10 km, with an obligatory minimum flight height of 300 resp.…”
Section: Present State Of Knowledgementioning
confidence: 99%